Hubungan Perilaku Kecanduan Game Online Dengan Gangguan Emosional Pada Remaja Di SMA Negeri 1 Kota Bengkulu Tahun 2025 - Dwi Inka Christie; Berlian Kando Sianipar; Nuche Marlianto (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Adolescents are an age group vulnerable to emotional disorders due to physical, psychological, and social changes (WHO, 2020). One factor suspected of contributing to the emergence of emotional disorders in adolescents is online gaming addiction. Excessive online gaming use can affect emotional regulation, increase anxiety, and impact behavior and academic achievement. This study aims to determine the relationship between online gaming addiction and emotional disorders in adolescents at SMA Negeri 1 Bengkulu City in 2025. This study used an analytical design with a cross-sectional approach. The study population was all students at SMA Negeri 1 Bengkulu City, with a sample size of 90 respondents drawn using a purposive sampling technique. The research instruments were an online gaming addiction questionnaire and an emotional disorders questionnaire. Data analysis was conducted using univariate and bivariate methods, using the Chi-Square statistical test at a significance level of α = 0.05. The results showed that the majority of respondents had a level of online gaming addiction, with frequencies ranging from 0 = ≤40%, 1 = 41-70%, and 2 = ≥71%. Respondents also experienced emotional disturbances with a frequency of 0 = Normal (0-16), 1 = Borderline (17-33), 2 = Abnormal (34-50). The results of the Chi-Square statistical test showed a p-value of 0.001 (p < 0.05), indicating a significant relationship between online gaming addiction and emotional disturbances in adolescents. Adolescents with high levels of online gaming addiction had a greater risk of experiencing emotional disturbances than adolescents with low levels of addiction. The conclusion of this study is that there is a significant relationship between online gaming addiction and emotional disturbances in adolescents at SMA Negeri 1 Kota Bengkulu in 2025. An active role is needed for schools, families, and health professionals in preventing and controlling online gaming use to maintain adolescents' emotional health.